Analysis of Retrieved Growth Guidance Sliding LSZ-4D Devices for Early Onset Scoliosis and Investigation of the Use of Nitinol Rods for This System. Issue 1 (1st January 2015) - Lukina, Elena; Kollerov, Mikhail; Meswania, Jay; Wertheim, David; Mason, Peter; Wagstaff, Paul; Laka, Aleksandr; Noordeen, Hilali; Yoon, Wai Weng; Blunn, Gordon
<x xml:space="preserve">Abstract</x> Study Design. Analysis of volumetric wear loss of retrieved growth guidance sliding devices LSZ-4D for treatment of early onset scoliosis and laboratory in vitro wear test for comparison of wear resistance of alloys Nitinol, Ti, and cobalt chromium (CoCr). Objective. To evaluate quantitatively the amount of wear debris from the sliding LSZ-4D device and to investigate the potential of using Nitinol for replacing Ti alloys in spinal instrumentation. To do that, wear resistance of Nitinol, Ti, and CoCr was compared. Summary of Background Data. There are little data regarding the amount of wear debris associated with growth guidance sliding devices for patients with early onset scoliosis and the wear resistance of superelastic Nitinol compared with Ti and CoCr. Methods. Volumetric wear loss was measured on LSZ-4D devices made from titanium alloy Ti6Al4V and each consisted of 2 rectangular section (6 × 4 mm) rods and 40 ± 8 fixture elements (20 ± 4 hooks and 20 ± 4 clips) retrieved from 3 patients (implantation period, 3.5–5.8 yr). Images of wear scars were taken on Bruker interferometer microscope and incorporated into MATLAB software. Wear resistance of Nitinol, Ti, and CoCr was studied using reciprocation pin-on-disk wear test in bovine serum at 37°C ± 1°C. Results. The volume wear rate of LSZ-4D device was found to be 12.5 mm3 per year from which 5 mm3 per year is the wear debris of the rod and 7.5 mm3 per year is the contribution of fixtures. Wear resistance of Nitinol is 100 times higher than that of Ti and comparable with that of CoCr. Conclusion. Application of wear-resistant coatings on Ti components in growth guidance sliding devices for the treatment of early onset scoliosis will be useful. High wear resistance of Nitinol combined with its superelastic and shape memory properties could make application of Nitinol rods for spinal instrumentation beneficial. Level of Evidence: 5